Immunity and protection of mice against Neisseria meningitidis group B by vaccination, using polysaccharide complexed with outer membrane proteins: a comparison with purified B polysaccharide. - Moreno, C (1985)
A methodology for preparing outer membrane proteins (type specific) complexed to group B polysaccharide of Neisseria meningitidis is described. These complexes, low in nucleic acid and lipopolysaccharide content, were immunogenic in mice with induction of humoral antigroup B and antiprotein responses. Immunized mice were also protected against challenge with N. meningitidis group B strains of the same or a different type from that used for vaccination. Both immunity and protection were enhanced when the mice received a secondary immunization with the protein-polysaccharide complex. Additional data have shown the capacity of purified B polysaccharide to induce immunological memory, even though it is incapable of inducing a humoral response when given alone.